Prevalence and sociodemographic correlates of vaginal discharge among married women of reproductive age group at a teaching hospital - Guntoory, Indira; Tamaraba, Narasinga R.; Nambaru, Lakshmana R.; Kalavakuri, Alina S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Vaginal discharge is the commonest reproductive tract infection among rural women in many community based studies in India. Recent evidence shows that the association between vaginal discharge and reproductive tract infection is weak. Psychosocial factors also contribute to vaginal discharge. So, the problem of vaginal discharge can be best understood not only in the biomedical perspective but also in the socio-cultural perspective. Proper understanding of this problem helps in initiating appropriate medical education programmes and framing health policies. This study is aimed to determine the prevalence of vaginal discharge, the socio demographic factors associated with it, women’s perceptions of vaginal discharge and their treatment seeking behaviour. Methods: This is a hospital based cross sectional study conducted in the outpatient department of Obstetrics and Gynaecology, MIMS, Nellimarla, Vizianagaram district of Andhra Pradesh. Women with the complaint of vaginal discharge were interviewed with a pretested questionnaire and sociodemographic details, details of obstetric history and contraceptive practices, personal and menstrual hygiene were noted. Statistical analysis of the significance of association of different variables was done. Results: The prevalence of vaginal discharge was found to be 28.99%. Its prevalence was found to be more in the younger age group, illiterate, women belonging to lower socioeconomic status and those who were married at less than 18 years of age. History of induced abortion, home deliveries, permanent method of sterilization, availability of toilet facility at home were significantly associated with vaginal discharge. Lower abdominal pain, dysuria and backache were the most prevalent co-morbidities with vaginal discharge. Conclusions: Improvement of the literacy rate, economic status and women’s empowerment will help to mitigate the problem of vaginal discharge.